This fissured land an ecological history of India - Gadgil, Madhav; Guha, Ramachandra (New Delhi ; Oxford : Oxford University Press, 2013)
This text presents an interpretative ecological history of the Indian subcontinent. Using a general theory of ecological history, the authors provide a fresh interpretation of India's history, including an ecological account of the caste system and a sociological analysis of resource use.
Previous ed.: 1992.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Includes bibliographical references and index.
Keywords: Human ecology -- India -- History; Forests and forestry -- India -- History; Natural resources -- India -- History